NTRK3-rearranged spindle cell neoplasm of the skin - Coutada, Andreia (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2025)
Neurotrophic tyrosine receptor kinase-rearranged spindle cell neoplasms (NTRK-RSCNs) are an emerging category of rare soft tissue tumors recently recognized by the World Health Organization Classification of Soft Tissue and Bone Tumours. NTRK-RSCNs mostly affect the superficial soft tissues of the extremities and trunk, and they can occur across a broad age range. These tumors exhibit a wide morphologic spectrum, often mimicking other mesenchymal tumors. Recognition of NTRK-RSCNs is crucial for targeted therapy in selected cases, given the recent approval of kinase inhibitors. We describe the case of a 55-year-old male with an NTRK-RSCN located on the arm, harboring the novel fusion partner PPFIBP1::NTRK3, while providing additional clinical and morphological characteristics of this rare entity.
Keywords: case report; cutaneous spindle cell neoplasm; kinase fusion neoplasm; kinazna fuzijska novotvorba; kožna neoplazma vretenastih celic; NTRK3; prikaz primera; soft tissue tumor; tumor mehkega tkiva